Peculiarities of physical rehabilitation of persons with impingement-syndrome of the shoulder joint - Zviriaka, Oleksandr; Rudenko, Anna (Journal of Education, Health and Sport, 2017)
The impingement syndrome of the shoulder joint is a common problem, which may lead to more serious pathology and disability. The main causes of impingement syndrome development are the shoulder joint injury or the features of professional and sports activities. The process of physical rehabilitation of individuals with impingement syndrome is a multi-stage approach aimed at returning to the previous level of functioning. Purpose. Determine the features of physical rehabilitation of individuals with impingement syndrome of the shoulder joint. Materials and methods of research: analysis, synthesis and generalization of scientific and methodical literature. Results. Functional constraints in impingement syndrome are characterized by loss of subacromial space due to changes in the humeral biomechanics of the shoulder joint, instability of the shoulder joint and / or muscular imbalance. According to age-related changes there are three stages of this pathology, every of which has certain structural and functional changes. The effectiveness of the process of physical rehabilitation is based on the identification of the etiological factor with the subsequent creation of an individual recovery program. Physical rehabilitation consists of three stages with gradual increase and complication of exercises. Conclusions. Physical rehab can effectively return the usual level of activity of everyday life of patients with impingement syndrome due to elimination of such manifestations as pain, reduced muscle strength, reduced amplitude of movements.